2004
DOI: 10.1111/j.1365-2125.2004.02102.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic polypharmacy in patients with schizophrenia: a multicentre comparative study in East Asia

Abstract: AimsPrevious studies of the prescription patterns of psychotropic medications in patients with schizophrenia have highlighted a high rate of antipsychotic polypharmacy, but data in Asia are sparse. This study seeks to examine the prevalence of antipsychotic polypharmacy in patients with schizophrenia and compare the differences between patients receiving one vs. those receiving more than one antipsychotic. MethodsAntipsychotic prescription for a sample of 2399 patients with schizophrenia from six countries and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
111
3
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 27 publications
(32 reference statements)
8
111
3
2
Order By: Relevance
“…Besides the differences in antipsychotic prescribing patterns between Japan and other countries [25,26], we also found in this study that the research paper productivity on SGAs was different from Japan to other Asian countries/areas such as Taiwan [11]. But we trust that research in this field will possibly continue to grow in the coming years, bearing in mind that the ideal antipsychotic drug has not yet been found [5] and that etiopathogeny of schizophrenia is still mostly unknown.…”
Section: Discussionmentioning
confidence: 91%
“…Besides the differences in antipsychotic prescribing patterns between Japan and other countries [25,26], we also found in this study that the research paper productivity on SGAs was different from Japan to other Asian countries/areas such as Taiwan [11]. But we trust that research in this field will possibly continue to grow in the coming years, bearing in mind that the ideal antipsychotic drug has not yet been found [5] and that etiopathogeny of schizophrenia is still mostly unknown.…”
Section: Discussionmentioning
confidence: 91%
“…The rate of polypharmacy (>4 medications) in this aforementioned country is high. Sim et al (2004) found polypharmacy to occur at a rate of 45.7 % in elderly and chronically ill patients 28 . Singapore researchers have reported the rate of polypharmacy in their people to be 59% in previous years and 73% in 2000 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Sim et al (2004) found polypharmacy to occur at a rate of 45.7 % in elderly and chronically ill patients 28 . Singapore researchers have reported the rate of polypharmacy in their people to be 59% in previous years and 73% in 2000 29 . By studying the literature, we were encouraged to examine the benefits of replacing polypharmacy with a single medication in elderly patients with chronic schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…The types or dose of medications were decided or adjusted by their primary treating teams based on clinical needs. The doses of antipsychotic medication were recorded and converted into equivalent doses of chlorpromazine dose (Sim et al 2004).…”
Section: Medicationsmentioning
confidence: 99%